Potential Output and Output Gap Estimates for Nepal - Poudyal, Pradeep Raj; Budha, Birendra Bahadur; Silpakar, Sajana; Bhatta, Siddha Raj; Thapa, Nara Bahadur (NRB Economic Review, 2017)
Estimation of potential output and output gap is one of the key issues for the conduct of macroeconomic policies and structural reforms in the long-run as the idea of output gap helps decide on the stance of such policies. A positive output gap, for instance, indicates that aggregate demand exceeds the productive capacity of the economy resulting into inflationary pressure. In contrast, a negative output gap is associated with recession, spare capacity, disinflation, and unemployment rate above the non-accelerating inflation rate of unemployment. In case of Nepal, the potential output grew by 4.3 percent during 1976-2017. While potential output growth was above 4.5 percent during the 1980s and 1990s, fall in total factor productivity limited such growth to 4 percent on average after 2000. The results show that output gaps in Nepalese case are mainly determined by the supply shocks like weather conditions, natural disasters, and supply disruptions rather than fluctuations in aggregate demand.